2021
DOI: 10.3389/fmolb.2021.737472
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Network Analysis Reveals the Role of miR-223-5p During Diabetic Corneal Epithelial Regeneration

Abstract: Diabetes mellitus (DM) is a complex metabolic disorder. Long-term hyperglycemia may induce diabetic keratopathy (DK), which is mainly characterized by delayed corneal epithelial regeneration. MicroRNAs (miRNAs) have been reported to play regulatory roles during tissue regeneration. However, the molecular mechanism by which miRNAs influence epithelial regeneration in DK is largely unknown. In this study, we performed miRNA and mRNA sequencing of regenerative corneal epithelium tissue from streptozotocin-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…We also screened differentially expressed miRNAs in the regenerated corneal epithelium of normal and type 1 diabetic mice, and found that miR-223-5p was significantly upregulated, which may be involved in regulating the delay of diabetic corneal wound healing. In the next validation experiment, we confirmed that inhibition of miR-223-5p accelerated the regeneration of diabetic corneal epithelium and nerves, which mediates inflammation response and epithelial cell proliferation through its target gene Hpgds (203). In 2016, our group also found that miR-204-5p, which can directly regulate sirt1, has increased expression in diabetic corneas, and inhibition of miR-204-5p promotes corneal epithelial regeneration by accelerating cell cycle (204).…”
Section: Mirnas and Long Noncoding Rnasmentioning
confidence: 54%
“…We also screened differentially expressed miRNAs in the regenerated corneal epithelium of normal and type 1 diabetic mice, and found that miR-223-5p was significantly upregulated, which may be involved in regulating the delay of diabetic corneal wound healing. In the next validation experiment, we confirmed that inhibition of miR-223-5p accelerated the regeneration of diabetic corneal epithelium and nerves, which mediates inflammation response and epithelial cell proliferation through its target gene Hpgds (203). In 2016, our group also found that miR-204-5p, which can directly regulate sirt1, has increased expression in diabetic corneas, and inhibition of miR-204-5p promotes corneal epithelial regeneration by accelerating cell cycle (204).…”
Section: Mirnas and Long Noncoding Rnasmentioning
confidence: 54%
“…Since corneal wound healing is a complex process involving multiple sequential and parallel pathways, ribonucleic acids‐based therapies seem to be an attractive modality to multi‐targeted regulating several processes simultaneously for solving wound healing problems. Substantial studies have reported that several miRNAs were involved in the process of corneal healing, such as miR‐223, [ 22 ] miR‐21, [ 7 ] and miR‐31. [ 23 ] However, miRNA therapy still faces challenges.…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-223-5p, which has a network communication relationship with hsa_circRNA_104175, was significantly lower in megakaryocytes treated with high glucose. This suggests that miR-223-5p can negatively regulate platelet formation and affect platelet morphology and function in diabetic hyperglycemia, thereby accelerating atherosclerosis in peripheral tissues and promoting arterial thrombosis ( 34 ). The miR-223-5p of bone marrow derived can regulate the apoptosis and proliferation of vascular endothelial cells, that realize through NOD-like receptor signaling pathway of vascular endothelial cells and participate in the process of vascular injury in vascular related diseases ( 35 ).…”
Section: Discussionmentioning
confidence: 99%